1984
DOI: 10.2307/3576412
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Organically Bound Tritium in Man

Abstract: The classic methodology for estimating dose to man from environmental tritium assumes that all tritium, whether organically bound or free, enters directly into man's free body water compartment and is uniformly distributed as tritiated water. This methodology ignores the fact that organically bound tritium in foodstuffs may be directly assimilated in the bound compartment of tissues without previous oxidation. A four-compartment model consisting of a free body water compartment, two organic compartments, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…For example, tritium incorporation into tissues of rats, rabbits, pigs, and calves exposed for an extended period to OBT in food was generally 4-10 times higher than after similar exposure to tritiated water (Kirchmann et al 1977;Rochalska and Szot 1977;Pietrzak-Flis et al, 1978;. Etnier et al (1984) concluded from a review of biokinetic data for tritium that intake of OBT in food could result in absorbed doses up to about five times higher than intake of tritiated water. Because available data on the biokinetics of OBT vary considerably with the compound administered, and because the ICRP's model for OBT is based mainly on observations of the behavior of selected compounds in laboratory animals, the model for OBT seems considerably less reliable than that for tritiated water.…”
Section: Organically Bound 3 H (Obt)mentioning
confidence: 99%
“…For example, tritium incorporation into tissues of rats, rabbits, pigs, and calves exposed for an extended period to OBT in food was generally 4-10 times higher than after similar exposure to tritiated water (Kirchmann et al 1977;Rochalska and Szot 1977;Pietrzak-Flis et al, 1978;. Etnier et al (1984) concluded from a review of biokinetic data for tritium that intake of OBT in food could result in absorbed doses up to about five times higher than intake of tritiated water. Because available data on the biokinetics of OBT vary considerably with the compound administered, and because the ICRP's model for OBT is based mainly on observations of the behavior of selected compounds in laboratory animals, the model for OBT seems considerably less reliable than that for tritiated water.…”
Section: Organically Bound 3 H (Obt)mentioning
confidence: 99%
“…Other h parameters are derived from steady-state distributions of tritium activity. Etnier et al [1984] report the following values (with units of day-1): Aud is equal to 0.0005463,hzy;f is equal to 0.00416, hfi is equal to 1.5472, and 3Lfi is equal to 0.10328.…”
Section: Tritium Metabolism and Dosimetrymentioning
confidence: 99%
“…To properly assess combined exposures to HTO and OBT, we describe the retention of tritium following exposure with a model that accounts for intake of both. Following the recommendation of Hill and Johnson [1993], we use the four-compartment model proposed by Etnier et al [1984] to describe tritium retention. One compartment is used to represent the retention of tritium in body water and the other three compartments are used to represent the retention of tritium in different types of organic molecules.…”
Section: Tritium Metabolism and Dosimetrymentioning
confidence: 99%
“…7) The most famous three-compartment model proposed by Bennett is usually called the NCRP model 8,9) shown in Fig. 2(b).…”
Section: Compartment Model Proceduresmentioning
confidence: 99%